KLASIFIKASI TUTUPAN LAHAN TAHUN 2021 DENGAN METODE RANDOM FOREST (RF) DAN SUPPORT VECTOR MACHINE (SVM) (STUDI KASUS: KOTA MATARAM) - Muhammad Anis Raihan; Husnul Hidayat; Hepi Hapsari Handayani (Institut Teknologi Sepuluh Nopember, 2025)
Land cover is all types of features that exist on the earth's surface on certain land, either artificial or natural. Information related to monitoring and processing satellite image data to obtain land cover classification can be done in various ways, one of which is machine learning methods. This study aims to apply machine learning methods in monitoring land cover using Landsat-8 imagery, to obtain a technique that has high accuracy and is suitable for monitoring land cover. This study uses machine learning methods, namely Support Vector Machine (SVM) and Random Forest (RF). The classification of land cover in this study consists of five classes, namely, built-up areas, water bodies, vacant land, agriculture, and vegetation, where the determination of this land cover class is based on the type of land cover that exists on the RTRW Map of Mataram City in 2011-2031. match the image used. This study shows that the method with the best accuracy is the Support Vector Machine (SVM) method with overall accuracy and kappa accuracy values of 0.9101 and 0.8748. However, there is a misclassification caused by several factors such as the reflectance value of each pixel which is almost the same, the cropping period, and other factors. These factors need to be considered because they affect the land cover classification results.